POLA DAN KARAKTER KEPEMIMPINAN WANITA MENURUT HAKIM-HAKIM 4 – 5 - Tuminah, Sri (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2023)
Abstract. Leadership is connected with who is the leader and who are the followers. It also related with the influence of the leader. Woman leadership is controversial issue especially within patriarchal culture. While The bible doesn’t explain about leadership, It’s telling the story and giving life examples about leadership which mostly are male leadership. So where is the role for woman leadership in the bible? The bibilcal study of Judges 4-5 was done to find a pattern and character that was shown by Deborah, a woman leader. The bible record that Deborah “was leading Israel at that time” Judges 4:4 . That explain that Debora takes the role of leader for Israel in the time of judges. From her story we can study how she led and the pattern that she used as woman leader, that is “a team leadership” where she led Israel side by side with Barak.